2018
DOI: 10.21037/tro.2018.07.03
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes for pediatric pineoblastoma: a single institute experience in Taiwan

Abstract: Background: Our purpose was to evaluate the clinical outcomes of pediatric pineoblastoma patients after multimodality treatment. Methods: The medical records of 11 children with pineoblastomas treated at Taipei Veterans General Hospital between 1991 and 2006 were retrospectively reviewed. There were 7 females (63.6%) and 4 males (36.4%) with a median age at diagnosis of 5.25 years (range, 1.47-16.8 years). Age, sex, symptoms, pathological findings, treatment modalities, failure patterns, recurrence date, death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…and children under 3 years of age who were treated according to infant brain tumor protocols with intensive chemotherapy alone (33). Surprisingly, Kang et al (44) in their study found that long-term survival can be achieved for patients who received multimodality treatment, and the results of their study revealed that the median overall survival was 2.3 years, with 2-and 5-year survival rates of 63.6 and 36.4%, respectively, after multimodality treatment. Lee et al (1) treated 34 adult patients with PB with cranial irradiation therapy and complete surgical resection, and the median survival time was 25.7 months.…”
Section: Discussionmentioning
confidence: 98%
“…and children under 3 years of age who were treated according to infant brain tumor protocols with intensive chemotherapy alone (33). Surprisingly, Kang et al (44) in their study found that long-term survival can be achieved for patients who received multimodality treatment, and the results of their study revealed that the median overall survival was 2.3 years, with 2-and 5-year survival rates of 63.6 and 36.4%, respectively, after multimodality treatment. Lee et al (1) treated 34 adult patients with PB with cranial irradiation therapy and complete surgical resection, and the median survival time was 25.7 months.…”
Section: Discussionmentioning
confidence: 98%
“…Of the 2701 articles retrieved in the search, 44 studies with IPD on 298 patients with pineoblastoma were included in the systematic review ( Table 1 ) [ 5 , 6 , 8 , 9 , 10 , 11 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. Figure 1 presents the PRISMA flowchart for this systematic review [ 18 ].…”
Section: Resultsmentioning
confidence: 99%